Radiofrequency inferior turbinate reduction improves smell ability of patients with chronic rhinitis and inferior turbinate hypertrophy - Assanasen, Paraya (OceanSide Publications, Inc., 2014)
Radiofrequency inferior turbinate reduction (RFITR) of inferior turbinate hypertrophy (ITH) is an effective way to treat patients with intractable nasal mucosal obstruction. The objective of this study was to assess smell ability, nasal symptoms, inferior turbinate grading (ITG), peak nasal inspiratory flow (PNIF) of patients with chronic rhinitis (CR), and ITH before and after RFITR. Patients with CR and ITH, aged 18–60 years, who underwent RFITR, were prospectively recruited. Smell ability (measured by smell detection threshold [SDT]), visual analog scale (VAS) of nasal symptoms, ITG, and PNIF before and 6–10 weeks after RFITR were compared. Forty-eight subjects were included. All nasal symptoms were significantly decreased after RFITR. After surgery, SDT (tested by phenyl ethyl alcohol) was worsened in 7 patients (14.6%), improved in 8 patients (16.7%), and did not change in 33 patients (68.7%). SDT after RFITR of six patients in the worsened SDT group were still within normal range (> −6.5). There was only one patient whose SDT changed from normosmia to mild hyposmia (−7.25 to −5.38). In the improved SDT group, two of eight patients had obviously better SDT after RFITR, which changed from moderate hyposmia to normosmia (−3.65 to −10; −3.73 to −10), whereas six of eight patients had little better SDT after RFITR. RFITR also significantly reduced ITG and improved PNIF. In conclusion, the treatment of patients with CR and ITH with RFITR significantly improved PNIF, ITG, and nasal symptoms assessed by VAS, although SDT after RFITR could be the same or improved or worsened.